Escape routes design specification analysis for optimum evacuation of 200 people in high-rise building - Mohamad Yatim, Yahya (Faculty of Built Environment, UTM, 2008)
Current issues in evacuation from the high-rise buildings, i.e. to either evacuate using staircase or elevator, the condition of escape routes provided in high-rise residential buildings, and people’s attitude toward fire safety, are still being debated by many parties. Escape routes in high-rise residential buildings is an important element for emergency escape. In this paper analysis of the specification of staircase, fire door and corridor will be carried out by simulating a number of people evacuating buildings of different layouts identified in the observation study.